2019
DOI: 10.1097/md.0000000000017512
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative evidence for association of sepsis and retinopathy of prematurity

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 56 publications
2
28
1
Order By: Relevance
“…34 Studies showed that sepsis increases the risk of development of any stage of ROP. 35 Our study also strongly supports sepsis as the independent risk factor for ROP. But it is difficult to adjust the impact of the use of oxygen and mechanical ventilation on the development of ROP and so the bias exist.…”
Section: Discussionsupporting
confidence: 81%
“…34 Studies showed that sepsis increases the risk of development of any stage of ROP. 35 Our study also strongly supports sepsis as the independent risk factor for ROP. But it is difficult to adjust the impact of the use of oxygen and mechanical ventilation on the development of ROP and so the bias exist.…”
Section: Discussionsupporting
confidence: 81%
“…Established risk factors include low gestational age (GA) and low birth weight, especially for infants who have a body weight < the 10th percentile [5]. Similarly, O 2 administration and hyperoxia [5] are further risk factors, while the role of sepsis [6] is equivocal. Currently, there is debate on whether RBC or platelet (PLT) transfusion increases the risk of developing ROP.…”
Section: Introductionmentioning
confidence: 99%
“…Study by Huang et al showed increased incidence of any form of ROP and severity with associated Sepsis. 20 Incidence of ROP was higher in babies having shock and requiring Ionotropic support than those without shock. Stage II or higher of ROP was significantly higher in cases with shock (66.7%) compared to the cases with no shock (29.4%).…”
Section: Nomentioning
confidence: 91%